A Lightweight Battery for Backpack Electrofishing. (26th February 2013) - Hockersmith, Eric E.; Brooks, Gabriel; Dumdei, Nathan D.; Achord, Stephen
Abstract: A lithium ion battery was modified to replace the conventional sealed lead acid battery used to operate a backpack electrofishing unit. Specifications and performance of the lithium ion battery were compared with those of a lead acid battery of similar capacity. The lithium ion battery was 76% lighter in weight than the lead acid battery, reducing the overall weight of a Smith‐Root model 12 backpack electrofishing unit and battery by 55%. Including the cost of a charger and parts to make the battery compatible with an electroshocking unit, the lithium ion battery and charger cost was 26% less than that of the lead acid battery and charger. Bench tests indicated the lithium ion battery provided 91% and 98% of the operating time of the lead acid battery per charge when the settings were 300 V at 90 Hz and 500 V at 90 Hz, respectively. The fuel gauge (battery discharge indicator) on the lithium ion battery, which was absent in the lead acid battery, provided the ability for a user to assess the remaining charge level while in the field. The lithium ion battery provided similar performance with a significant reduction in weight and cost compared with a conventional lead acid battery for backpack electrofishing. The lighter weight of the backpack electrofishing unit using the lithium ion battery can reduce fatigue and the risk of fatigue‐related injuries to field crews. Received March 23, 2012; accepted January 7, 2013